1991
DOI: 10.1073/pnas.88.23.10605
|View full text |Cite
|
Sign up to set email alerts
|

Ring fission of anthracene by a eukaryote.

Abstract: Ligninolytic fungi are unique among eukaryotes in their ability to degrade polycyclic aromatic hydrocarbons (PAHs), but the mechanism for this process is unknown. Although certain PAHs are oxidized in vitro by the fungal lignin peroxidases (LiPs) that catalyze lig olysis, it has never been shown that LiPs initiate PAH degradation in vivo. To address these problems, the metabolism of anthracene (AC) and its in vitro oxidation product, 9,10-anthraquinone (AQ), was examined by chromatographic and isotope dilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 19 publications
5
75
0
3
Order By: Relevance
“…The latter is not surprising since APO does neither possess a dioxygenaselike activity to cleave the ring (Vaillancourt et al 2006) nor an epoxide hydrolase activity that forms dihydrodiols (Yang 1988). One quinone has been detected during Ant oxidation (traces of putative 1,4-anthracenedione) that is in accordance with previous findings on naphthalene ) but differs from reports on LiP and MnP, where 1,9-anthraquinone was the typical quinoid product of Ant oxidation (Hammel et al 1991;Kotterman et al 1994;Eibes et al 2006) or Laccases (Collins et al 1996).…”
Section: Discussionsupporting
confidence: 74%
“…The latter is not surprising since APO does neither possess a dioxygenaselike activity to cleave the ring (Vaillancourt et al 2006) nor an epoxide hydrolase activity that forms dihydrodiols (Yang 1988). One quinone has been detected during Ant oxidation (traces of putative 1,4-anthracenedione) that is in accordance with previous findings on naphthalene ) but differs from reports on LiP and MnP, where 1,9-anthraquinone was the typical quinoid product of Ant oxidation (Hammel et al 1991;Kotterman et al 1994;Eibes et al 2006) or Laccases (Collins et al 1996).…”
Section: Discussionsupporting
confidence: 74%
“…Research about the biodegradation of ANTH by Hammel et al [23] revealed that ANTH had almost no biodegradation over a 15-day culture period and degraded slowly such that 30% has been removed after 30 days. While in contrast, 9,10-anthracenedion showed a much better rate of degradation, rapidly degraded by above 80% in only 16 days.…”
Section: Identification Of the Anth-clo 2 Reaction Productsmentioning
confidence: 98%
“…To determine whether such a new pathway exists, we investigated anthracene metabolism in P. chrysosporium (10). 14C-labeled anthracene and anthraquinone (0.2 pM) were supplied to ligninolytic (nitrogen-limited) cultures, and it was shown that '4Co2 evolution from the two compounds was similar (-13% in 14 days).…”
mentioning
confidence: 99%